2020
DOI: 10.1089/ten.tea.2020.0041
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Effects on Mesenchymal Stem Cell Osteogenesis in a Three-DimensionalIn VitroBone Model

Abstract: As musculoskeletal (MSK) disorders continue to increase globally, there is an increased need for novel, in vitro models to efficiently study human bone physiology in the context of both healthy and diseased conditions. For these models, the inclusion of innate immune cells is critical. Specifically, signaling factors generated from macrophages play key roles in the pathogenesis of many MSK processes and diseases, including fracture, osteoarthritis, infection etc. In this study, we aim to engineer three-dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 31 publications
4
26
0
Order By: Relevance
“…A recent study found that co-cultured macrophages and mesenchymal stem cells can be induced to undergo osteogenic differentiation, with M2 macrophages being the most successful at promoting the generation of new bone tissue ( Loi et al, 2016 ; Zhang et al, 2017 ; Nathan et al, 2019 ). Furthermore, quite a few studies have shown that an initial proinflammatory phase modulated by M1 macrophages promotes osteogenesis in BMSCs ( Tu et al, 2015 ; Lu et al, 2017 ; Romero-López et al, 2020 ; Xia et al, 2020 ). However, the mechanism of M1 macrophages promoting osteogenic differentiation at the early stage of inflammation is still rather ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that co-cultured macrophages and mesenchymal stem cells can be induced to undergo osteogenic differentiation, with M2 macrophages being the most successful at promoting the generation of new bone tissue ( Loi et al, 2016 ; Zhang et al, 2017 ; Nathan et al, 2019 ). Furthermore, quite a few studies have shown that an initial proinflammatory phase modulated by M1 macrophages promotes osteogenesis in BMSCs ( Tu et al, 2015 ; Lu et al, 2017 ; Romero-López et al, 2020 ; Xia et al, 2020 ). However, the mechanism of M1 macrophages promoting osteogenic differentiation at the early stage of inflammation is still rather ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…These 3D constructs were then cultured in a custom-designed, dual-flow microphysiological system. Figure 1 a shows the loading process of the scaffold-based 3D cultures [ 13 ]. The medium was perfused into the scaffold chamber from both the upper and lower inlets, as shown in Figure 1 b.…”
Section: Resultsmentioning
confidence: 99%
“…Here we discuss in more detail models of the gut, brain, lungs, and vasculature with an integrated immune element. The role of macrophages has also been examined in models of osteogenesis and muscle repair (113)(114)(115)(116)(117) but is outside the scope of this review.…”
Section: Context Ii: Models Of Peripheral Tissues With Immune Elementsmentioning
confidence: 99%